Giordano Bruno and his Conception of Infinity of the Reality - Castro, Manuel Cabada (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
Giordano Bruno, in its basis of created reality as infinite, uses a series of metaphysical reasons which are closely in relation with the conception of divinity as infinite in itself. In consequence, the reality which has its origin in divinity has to be thought also as possessing in some way the character of «infinite». In this way, in Bruno, is given a simultaneous process of closeness to traditional neoplatonism or augustinianism and decisive distancing from aristotelianism. The result is a magnificent vision of reality which appears in the brunian system as created icon of the same infinity of the divinity without identifying itself pantheistically with it.